Sukuk as an attractive alternative of funding and investment in Tunisia / Hajer Chermia and Yacin Jerbi - Jerbi, Yacin (Faculty of Business and Management, 2015)
During the past decade, the Islamic finance industry has witnessed significant developments, particularly in the field of Sukuk (Islamic bonds). Sukuk represent one of the most successful products in Islamic finance. They have attracted the attention of several investors and become increasingly popular in various markets worldwide. They have gained prominence as financial instruments serving both government funding through the issuance of sovereign sukuk and private sector funding through corporate sukuk. This paper starts by providing a brief overview on the sukuk structuring and on the major developments in the flourishing world Islamic capital market. It then investigates the Malaysian sukuk market, with special focus on the key factors contributing to its successful experience. The paper concludes by explaining the ways through which sukuk represent an attractive alternative of funding and investment for Tunisia, taking into account that Tunisia is preparing for its first issuance of sovereign sukuk in the second term of 2013. The promising potential sukuk is also demonstrated through comparing measures taken by the Tunisian and Malaysian governments.